Live weight and body condition changes of Matebele does during their breeding cycle in a semi-arid environment - Sibanda, Lindiwe Majele; Bryant, M.J.; Ndlovu, L.R. (Elsevier, 2000)
The live weight of Matabele does kept in seven communally grazed flocks in southern Zimbabwe were established by survey over a two-year period. The does showed a cyclical change in weight around the breeding cycle, the mean live weight at mating, immediately after kidding and 60 days after kidding were 30.0, 35.2 and 32.8 kg, respectively. The month of mating and kidding had a major effect on live weight. The post-kidding weight of does kidding in the late-dry to early-wet season was approximately 25% less than that of does kidding at the end of the wet season. Does mating during the wet season had the greatest gains over the course of the breeding cycle. The mean mating weight of primiparous does was 24.0 kg, approximately two-third that of adult does. Younger does tended to gain more weight over the course of the breeding cycle than older does. There were consistent differences in live weight among flocks. The results illustrate the profound effects of seasonal factors on live weight changes and the abilities of Matabele goats to adapt to their harsh environment.